SELF REGULATED LEARNING DITINJAU DARI EFIKASI DIRI SISWA: SELF REGULATED LEARNING REVIEWED FROM STUDENT SELF EFFICATION - Andreas Yudha; Fery Nugroho (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2019)
Introduction: This is a study of improved quality of learning that comes to some of the factors called self-regulated learning and self-effication.Method: The research method was done with quantitative research methods with filling the Self Effication Scale and the Self-Learning Scale. The study participants were 120 around 11-15 year-old youths in three secondary schools in yogyakarta.Result: Results based on regression analysis showed that self-effication predicts the ability of self regulated learning. The two independent variables contribution amounts to 10,6% on dependent variables.Conclusion: Discussion of this study could be said that self-effication capabilities predict the abilities of self-regulated learning. Junior high school students realized their ability would make it easier to reform youth learning activities. Keyword: Self Efication, Self Regulated Learning ABSTRAK Pendahuluan Penelitian ini adalah penelitian mengenai tentang peningkatan kualitas belajar yang merujuk pada beberapa faktor yaitu self-regulated learning dan efikasi diri. Metode Penelitian ini dilakukan dengan metode penelitian kuantitatif dilakukan dengan pengisian skala efikasi diri dan Skala self regulated learning. Partisipan penelitian adalah 120 remaja berusia 11-15 tahun di tiga Sekolah Menengah Pertama di Yogyakarta. Hasil Berdasarkan analisis regresi menunjukan bahwa efikasi diri memprediksi kemampuan self-regulated learning. Kontribusi kedua variabel independen tersebut sebesar 10,6% pada variabel dependen. Kesimpulan dan Saran Pada penelitian ini dapat dikatakan bahwa kemampuan efikasi diri mampu memprediksi kemampuan self regulated learning. Remaja SMP menyadari akan kemampuan yang mereka miliki akan mempermudah dalam meregulasi kegiatan belajar remaja. Kata Kunci : Efikasi Diri, Self Regulated Learning,